Spontaneous membranous dysmenorrhea: a rare clinical entity - Sharmila, Vijayan; Thirunavukkarasu, Arun Babu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Membranous dysmenorrhea is a rare painful clinical condition associated with spontaneous expulsion of the endometrium as an entire piece, retaining the shape of the uterus. Authors report a case of membranous dysmenorrhea in a 36 year old multiparous woman, who was not on any hormonal therapy. She presented with history of menorrhagia for 20 days and severe dysmenorrhea for one day. During her second day of hospital admission, she expelled a fleshy mass resembling a decidual cast. Histopathological examination was consistent with diagnosis of membranous dysmenorrhea. The etiology of membranous dysmenorrhea is not very clear and hence reporting such rare cases may aid in understanding the etiology and pathophysiology of this rare condition.